Indonesian National Army Involvement in the Law Enforcement: Environmental Pollution in Citarum River - Diza Pratama; Viola Audy; Evanie Estheralda Elizabeth (Universitas Kuningan, 2020)
Citarum river, located in West Java, is the longest and the largest river in Indonesia. Nevertheless, it is also noted as the most polluted rivers in the world. The aims of this research are to know the steps and the efforts taken by the government in the manifestation of Citarum Harum program, to understand the legal basis or the legal form or legislation with the involvement of the Indonesian National Army, and to see the social impact of this program for the local community. The juridical-empirical research methodology in this study refers to a research method in the literature study and an interview to sources by asking several questions face to face. The findings showed the Government involvement in handling Citarum River is stipullated in the Presidential Regulation Number 15 of 2018, the acceleration of pollution control and damage of watershed. To tackle with the problem, the government hold a program called Citarum Harum. In addition, the involvement and the various efforts done by Indonesian National army members in the program is in accordance with the mandatory laws. It has a significant impact on the ecosystem and the local community.Sungai Citarum yang terletak di Jawa Barat merupakan sungai yang paling panjang dan paling besar di Indonesia. Namun sayangnya, Sungai Citarum tercatat sebagai salah satu dari sungai yang paling tercemar di dunia.. Tujuan penelitian ini untuk mengetahui langkah-langkah pemerintah dalam upaya mewujudkan program Citarum Harum, mengetahui dasar hukum dan kaitan hukum atau undang-undang dengan keterlibatan Tentara Nasional Indonesia dalam program Citarum Harum, dan mengetahui dampak sosial program Citarum Harum bagi masyarakat setempat. Metode penelitian hukum yuridis empiris yaitu metode penelitian studi kepustakaan dan wawancara yang dilakukan dengan mengajukan beberapa pertanyaan kepada narasumber secara langsung dengan bertatap muka. Hasil penelitian menunjukkan bahwa penanganan Sungai Citarum yang melibatkan pemerintah, yaitu Peraturan Presiden Nomor 15 Tahun 2018 tentang Percepatan Pengendalian Pencemaran dan Kerusakan Daerah Aliran Sungai Citarum dengan pemerintah juga mengadakan sebuah program untuk menanggulangi pencemaran dalam Sungai Citarum ini, yang diberi nama Citarum Harum dan keterlibatan anggota Tentara Nasional Indonesia dalam program Citarum Harum dalam melakukan berbagai upaya yang sesuai dengan amanah Undang-undang ini memberikan dampak yang cukup signifikan terhadap ekosistem dan juga sosial masyarakat setempat.